(untitled) (AYUSHDHARA, 2016)
The word Bandha means ‘binding’, ‘tying a bond’, ‘to catch’ or ‘damming of a river’, ‘building a bridge’. These are the specific positions of body by which energy of body is restored. Anatomically Bandha is the contraction of specific muscles of body. Mool Bandha is the principle, key and primary Bandha of the Yogic tradition. Moola means ‘ Root’, ‘Base’, or ‘Source’ and Bandha denotes ‘Lock’, ‘posture’, ‘bondage’ or ‘catching hold of’. Moola Bandha results from the contraction of muscles surrounding the perineal body, which lies between the anus and genitals Moola Bandha is associated with the centre of perineum i.e., site of Mooladhar chakra. This consists of a contraction, a muscular lifting-up in the pelvic floor. Pelvic floor consists of Levator ani and coccygeus muscles. Overstretching of pelvic floor muscles and fascia during childbirth and pregnancy, trauma or congenital defect in pelvic floor musculature or some surgical procedures can damage pelvic musculature or can cause pelvic organs prolapse. Moola Bandha specially contracts the levator ani muscles. This strengthens the pelvic floor and tones the pelvic organs, thus prevents pelvic organs prolapse, calms the autonomic nervous system, improves blood supply to pelvic organs, prevents flow of energy from body and restrains energy at perineum. Contraction of pelvic diaphragm muscles and anal sphincters tones and strengthens the uro-genital muscles, improves digestion and is also beneficial in conditions like haemorrhoids, constipation, hypertension, menstrual problems and anxiety.